THE INTERACTION OF COMPREHENSIVE SCHOOL AND TEACHERS’ TRAINING COLLEGE IN CONDITIONS OF FORMING A COMPLETE SOCIAL AND CULTURAL ENVIRONMENT OF A REGION - Lyudmila V. Vedernikova; Olga A. Povoroznyuk (Высшее образование в России, 2022)
The article is devoted to the problem of creating a complete social and cultural environment of aregion by means of organizing interaction of comprehensive school and pedagogical practice, which is accomplished on three levels of the process: a research one, an innovative and practical one, and the level of professional development.